Moving Towards Optimized Noncommunicable Disease Management in the ASEAN Region: Recommendations from a Review and Multidisciplinary Expert Panel - Castillo-Carandang NT; Buenaventura RD; Chia YC; Do Van D; Lee C; Duong NL; Ng CH; Robles YR; Santoso A; Sigua HS; Sukonthasarn A; Tan R; et al. (Dove Medical Press, 2020)
Nina T Castillo-Carandang,1 Robert D Buenaventura,2 Yook-Chin Chia,3 Dung Do Van,4 Cheng Lee,5 Ngoc Long Duong,6 Chee H Ng,7 Yolanda R Robles,8 Anwar Santoso,9 Helen S Sigua,10 Apichard Sukonthasarn,11 Roger Tan,12 Eka Viora,13 Hazli Zakaria,14 Grace E Brizuela,15 Priyan Ratnasingham,16 Mathew Thomas,17 Anurita Majumdar16 1Department of Clinical Epidemiology, College of Medicine, University of the Philippines Manila, Manila, Philippines; and Institute of Clinical Epidemiology, National Institutes of Health, University of the Philippines Manila, Manila, Philippines; 2Department of Psychiatry, Manila Theological College - College of Medicine, Manila, Philippines; 3Department of Medical Sciences, School of Healthcare and Medical Sciences, Sunway University, Bandar Sunway, Selangor, Malaysia; 4The University of Medicine and Pharmacy at Ho Chi Minh City, Ho Chi Minh City, Vietnam; 5National Addictions Management Service, Institute of Mental Health, Singapore; 6Department of Research, Education and Technology, Vietnam National Heart Institute, Hanoi, Vietnam; 7Department of Psychiatry, The Melbourne Clinic and St Vincent’s Hospital, University of Melbourne, Richmond, VIC, Australia; 8College of Pharmacy, University of the Philippines Manila, Manila, Philippines; 9Department of Cardiology, Vascular Medicine, National Cardiovascular Centre - Harapan Kita Hospital, Universitas Indonesia, Jakarta, Indonesia; 10University of the Philippines Open University, Laguna, Philippines; 11Department of Internal Medicine, Faculty of Medicine, Chiang Mai University, Chiang Mai, Thailand; 12Roger Kidney Clinic, Gleneagles Hospital, Singapore; 13Indonesia Psychiatrist Association, Jakarta, Indonesia; 14Department of Psychiatry, Faculty of Medicine, Universiti Kebangsaan Malaysia Medical Centre, Kuala Lumpur, Malaysia; 15Research, Development and Medical, Pfizer Upjohn, Manila, Philippines; 16Research, Development and Medical, Pfizer Upjohn, Singapore; 17Corporate Affairs, Pfizer Upjohn, SingaporeCorrespondence: Nina T Castillo-Carandang Tel +632-8-5254098Email ntcastillocarandang@up.edu.phIntroduction: Noncommunicable diseases (NCDs) are the leading cause of morbidity and mortality in the Association of Southeast Asian Nations (ASEAN) member states. Progress has been slow despite the World Health Organization action plan for the prevention and control of NCDs in the region. This paper presents recommendations focused on practical strategies for optimizing NCD management in the ASEAN region.Methods: A multidisciplinary group of experts from six ASEAN member states convened for two face-to-face meetings to discuss barriers and possible recommendations for optimizing NCD management, focused on cardiovascular diseases and mental disorders, in the region. Multiple approaches, ie, analysis of insights from the meetings and a review of existing literature on NCD programs in the ASEAN region were followed. The proposed recommendations were also based on selected successful interventions in ASEAN member states, thus providing actionable strategies.Results: The gaps identified in NCD management for cardiovascular diseases and mental disorders in the ASEAN region were classified into gaps relating to policies and to clinical and public health practice. The proposed solutions addressing policy gaps include fostering multisectoral public–private partnerships, employing “whole-of-government” and “whole-of-society” approaches and promoting “health-in-all policies approach” to manage issues with financing, accessibility, efficiency and quality of health services. Whereas proposed solutions to bridge clinical and public health practice gaps entail strengthening primary care services, building the capacity of trained healthcare workers and employing collaborative care for holistic management of patients.Conclusion: The scale of premature and preventable deaths from NCDs in the ASEAN region remains a serious public health concern and requires a “whole-of-system approach”. The interventions proposed in this paper build on regional collaborations and knowledge sharing to help develop a concerted and targeted response to NCDs.Keywords: cardiovascular disease, mental health, prevention strategies, public health